1998
DOI: 10.1105/tpc.10.8.1267
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+, Annexins, and GTP Modulate Exocytosis from Maize Root Cap Protoplasts

Abstract: Protoplasts isolated from root cap cells of maize were shown to secrete fucose-rich polysaccharides and were used in a patch-clamp study to monitor changes in whole-cell capacitance. Ca2+ was required for exocytosis, which was measured as an increase in cell capacitance during intracellular dialysis with Ca2+ buffers via the patch pipette. Exocytosis was stimulated significantly by small increases above normal resting [Ca2+]. In the absence of Ca2+, protoplasts decreased in size. In situ hybridization showed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 48 publications
2
55
0
Order By: Relevance
“…Results from the qRT-PCR were consistent with that obtained from the GeneChip experiments (Table 2). In addition, we showed that a number of genes previously reported by others as being highly expressed in the maize RC, were likewise upregulated in the RC microarray data (Supplement 1), including OS001597_r (ZmRCP1) (Matsuyama et al, 1999a), OS003906.1 (ZmRCP2) (Matsuyama et al, 1999a), OS007905 (ANNEXIN,) (Carroll et al, 1998), OS011991_i (GDP-D-Mannose-4,6-Dehydrogenase) (Ponce et al, 2000), and OS014195_i (ZmGRP4) (Matsuyama et al, 1999b), thereby providing further support for the reliability of the microarray data.…”
Section: Experimental Validation Of Differentially Expressed Genes Inmentioning
confidence: 80%
“…Results from the qRT-PCR were consistent with that obtained from the GeneChip experiments (Table 2). In addition, we showed that a number of genes previously reported by others as being highly expressed in the maize RC, were likewise upregulated in the RC microarray data (Supplement 1), including OS001597_r (ZmRCP1) (Matsuyama et al, 1999a), OS003906.1 (ZmRCP2) (Matsuyama et al, 1999a), OS007905 (ANNEXIN,) (Carroll et al, 1998), OS011991_i (GDP-D-Mannose-4,6-Dehydrogenase) (Ponce et al, 2000), and OS014195_i (ZmGRP4) (Matsuyama et al, 1999b), thereby providing further support for the reliability of the microarray data.…”
Section: Experimental Validation Of Differentially Expressed Genes Inmentioning
confidence: 80%
“…The calcium influx takes place only at the tips of growing root hairs (Herrman & Felle, 1995; Felle & Hepler, 1997). The high [Ca 2+ ] c is probably required for exocytosis (Carroll et al. , 1998).…”
Section: The Cytoskeleton In Growing Root Hairsmentioning
confidence: 99%
“…In mammals, annexins have been implicated in a number of membrane events including regulated and constitutive exocytosis, endocytosis and membrane organisation [7][8][9]. In plants, a role for annexins in membrane trafficking and/or secretion, calcium channel formation and calcium hemostasis has been suggested [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%